Psychosocial Distress and the Quality of Life of Cancer Patients in Rural Hospitals in Limpopo Province: A Qualitative Study - Dorah Ursula Ramathuba; Neo Jacqueline Ramutumbu (Current Oncology)
Background: The diagnosis and treatment of cancer are associated with substantial physical, psychological, and social morbidity for most patients. Distress can be seen as an unpleasant experience of an emotional, psychological, social, or spiritual nature that interferes with the ability to cope with cancer treatment. Purpose: The aim was to understand patients’ experiences of distress in their context and to analyze and interpret the findings. Method: An explorative, descriptive qualitative study was conducted among cancer patients receiving treatment and care at rural hospitals in Limpopo. A face-to-face individual interview was conducted to determine the participants’ cancer-related experiences and quality of life. Thematic analysis was conducted following Tesch’s method, and the themes developed were subjected to a triangulation process to ensure the validity and rigor of the findings. Findings: The participants revealed experiences of symptomatic distress resulting in biopsychosocial distress such as pain, fatigue, emotional distress related to prognosis and uncertainty about the future, psychosocial distress related to a lack or absence of support, financial instability, and poor self-esteem. Conclusions: Cancer patients face many challenges during their treatment journey. Participants were drained by anxiety and uncertainty of the cancer trajectory and required psychosocial support. The oncology team must provide supportive preventive measures for side effects management and culture-sensitive psychotherapy at an early stage to improve their quality of life.